Geospatial dimension of academic and social segregation on student achievement in secondary schools of Metropolitan Lima area - Muelle, Luis Edgardo (2023)
This study analyzes and compares the academic and social segregation by socioeconomic status among the districts o the Metropolitan Lima area, with respect to the student achievement in mathematics, reading and science tests applied during the 2019 School Census in the second grade of secondary education. To measure segregation, it uses the Dissimilarity index, which highlights the importance of private schools, the Mutual Information index that reports on inter-school and intra-school segregation and belonging to the same social category. Likewise, Moran’s autocorrelation index is presented, which visualizes the existence of socially and academically differentiated conglomerates according to the territorial location of the schools. These indices reveal a heterogeneous structure of segregation whose intensity varies according to the social composition of public and private schools in each district of the area. Geographic location patterns help to understand the effects of proximity and differentiation of social, school and residential profiles, and propose more geospatial interest to better monitor the functioning of schools and promote equality of learning.